Museums of language and the display of intangible cultural heritage - Sönmez, Margaret J.-M; Gahtan, Maia W. ca. 20./21. Jh; Cannata, Nadia 1963- (Routledge, Taylor & Francis Group, 2020)
"Museums of Language and the Display of Intangible Cultural Heritage presents essays by practitioners based in language museums around the world. Describing their history, mission, and modes of display, contributors demonstrate the important role intangible heritage can and should play in the museum. Arguing that languages are among our most precious forms of cultural heritage, the book also demonstrates that they are at risk of neglect, and endangerment from globalization and linguistic imperialism. Including case studies from across Europe, North America, Africa and Asia, this book documents the vital work being done by museums to help preserve languages and make them objects of broad public interest. Divided into three sections, contributions to the book focus on one of three types of museums: museums of individual languages, museums of language groups, both geographic and structural, or museums of writing. The volume presents practical information alongside theoretical discussions and state-of-the-art commentaries concerning the representation of languages and their cultural nature. Museums of Language and the Display of Intangible Cultural Heritage is the first volume to address the subject of language museums."
Keywords: Language and languages / Museums; Language and culture; Language maintenance; Museum exhibits; Sprache; Spracherhaltung; Museum; Immaterielles Kulturerbe